Controlling Greenhouse Environment For Green Rose Plantation Using Raspberry Pi Microcontroller And Sensor - Muhamat, Noor Alwani (Universiti Sains Malaysia, 2017)
Environment control is the one of the significant factors that needs to be controlled in green rose production. Before using the greenhouse technology, there are only 20 of green rose are successful grown from 100 of green rose. There is only 20% of successful growing green rose. Therefore, this research mainly focuses on an environment control automated device which is a system that applies automated control of the environment factors such as temperature, humidity and soil moisture by using microcontroller to provide optimum condition to green rose plantation. The aim of this project is to develop an automated greenhouse for green rose plantation in order to increase the green rose production. In this project, the greenhouse are developed by using WiBro module, DHT11 temperature and humidity sensor and soil moisture sensor. By using this device, the temperature, humidity and soil moisture level inside the greenhouse can be monitored through the internet. In addition to that, this system applies the concept Internet of Things (IoT) that enables users to monitor the environment condition inside the greenhouse anywhere whenever accessing the internet. Besides that, the device is also equipped with automatic mechanism to control the environmental condition inside the greenhouse to maintain the optimum conditions. The result obtained shows the increasing the successful growth green rose to 63 from 100 green rose tree. It means increasing by 315% of green rose plantation. Greenhouse technology is the best method to the farmer to increasing their production population.